Citrate synthase desuccinylation by SIRT5 promotes colon cancer cell proliferation and migration - Ren, Mengmeng; Yang, Xin; Bie, Juntao; Wang, Zhe; Liu, Minghui; Li, Yutong; Shao, Genze; Luo, Jianyuan (Biological chemistry, 2020)
Citrate synthase (CS), the rate-limiting enzyme in the tricarboxylic acid (TCA) cycle catalyzes the first step of the cycle, namely, the condensation of oxaloacetate and acetyl-CoA to produce citrate. The expression and enzymatic activity of CS are altered in cancers, but posttranslational modification (PTM) of CS and its regulation in tumorigenesis remain largely obscure. SIRT5 belongs to the nicotinamide adenine dinucleotide (NAD) -dependent deacetylase sirtuin family and plays vital roles in multiple biological processes via modulating various substrates. Here, we show that SIRT5 interacts with CS and that SIRT5 desuccinylates CS at the evolutionarily conserved residues K393 and K395. Moreover, hypersuccinylation of CS at K393 and K395 dramatically reduces its enzymatic activity and suppresses colon cancer cell proliferation and migration. These results provide experimental evidence in support of a potential therapeutic approach for colon cancer.